Analisis Kinerja PT PLN (Persero) Rayon Semarang Tengah - Irkham Nugroho Putro; Ida Hayu Dwimawanti; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Electricity is now become primary need that affect all of human activity. Based of the tendency of needs of electricity energy so large, so there is needed government role to fullfil society for it. Government Institution that responsible to provide electricity energy need is PT PLN (Persero) as public organization which is one of the government national corporate. One of electricity need provider is PT PLN(Persero) Semarang Central Rayon as the largest rayon in Semarang city. This research is based on problems of performance achievement from PT PLN (Persero) Semarang Central Rayon in 2014. This research aims to analyze the performance of PT PLN (Persero) Semarang Central Rayon and analyze factors that support and hinder the performance of PT PLN(Persero) Semarang Central Rayon as a provider of electrical energy needs. Assessment of the performance at PT PLN(Persero) Semarang Central Rayon are seen from responsiveness, responsibility, and accountability. Factors that affect the performance are seen from leadership, human resources and existing infrastructure. This research uses descriptive qualitative with the the subjects consists of four main informant. Based on result of research, the performance of PT PLN (Persero) Semarang Central Rayon is not optimal yet. So there are some suggestions that can be carried out to optimize its performance, such as utilizing GPS(Global Positioning Screen) application for technician to reach customer address. Establish procurement contract of goods with vendor . Renew contract system with framework contract system. Update the information data of perfomance display to optimize public transparency. Make a reward system directly from manager to the employees. Increase the quantity of employees by coordinating with PLN headquarter, and Providing facilities and infrastructure in order to increase organization performance.